PENGARUH LAMA PENGUKUSAN TERHADAP KUALITAS KERUPUK SINGKONG DENGAN BAHAN DASAR TEPUNG CASAVA - Yuyun Wahyuni (Agriculture Faculty of Flores University, 2019)
Cassava is also known as cassava, an annual tropical and sub-tropical tree from the Euphorbiaceae family. Tubers widely recognized as staple foods. Cassava has advantages compared to other food ingredients. Aside from being a staple food, many kinds of cassava processed products have utilized by our community, including cassava crackers. This study used a Completely Randomized Design (CRD) with 5 (five) treatments and 4 (four) replications or 5 x 4 to obtain 20 experimental units. The treatment factor is steaming length, which consists of 5 levels of steaming time as follows: A: 30 minutes, B: 60 minutes, C: 90 minutes, D: 120 minutes, E: 150 minutes. The quality of cassava crackers to be tested or measured based on their physical appearance is related to consumer acceptance. In conducting organoleptic testing, panelists influenced by several factors. Factors that influence panelists include physical factors and psychological factors. The organoleptic parameters observed included color, taste, and degree of crispness. Laboratory tests include carbohydrate tests, water content, ash content, protein, and fat content. The conclusion was that the effect of steaming time had no significant effect on moisture content, ash content, protein, and crispness, while the effect of steaming duration had a significant impact on the levels of fat, carbohydrate, taste, and color in cassava crackers. The best quality of the five treatments was treatment 5 (p5), ie, steaming time with 150 minutes